SAT0258 DRUG RETENTION RATE AND PROGNOSIS AFTER DISCONTINUATION OF INFLIXIMAB IN PATIENTS WITH BEHÇET SYNDROME. (13th June 2020) - Esatoglu, S. N.; Tukek, B.; Taflan, S. S.; Ozyazgan, Y.; Ucar, D.; Seyahi, E.; Melikoglu, M.; Hamuryudan, V.; Uygunoglu, U.; Siva, A.; Fresko, I.; Yurdakul, S.; et al.
Abstract : Background: Infliximab (IFX) has become an important treatment option for all manifestations of Behçet syndrome (BS). Adverse events, loss of efficacy, lack of patient compliance and cost may limit its sustained use in patients with BS. Objectives: We aimed to evaluate the drug retention rates, causes of discontinuation and outcome after cessation of IFX. Methods: We reviewed the charts of 850 patients with BS who were registered in our clinic between 2009 and 2013 and identified those who had used IFX. The charts of these patients were surveyed for demographic features, the reasons for IFX use, previous and concomitant drugs, IFX duration, reasons for discontinuation and time to flare after discontinuation of IFX. We defined flare as disease activity in the organ involvement that necessitated IFX use. New major organ involvement that developed during or after discontinuation of IFX were also be noted. Results: A total of 50/850 patients were treated with IFX (40 men, mean age 40±9.5 years), for uveitis (n=29), vascular involvement (n=11), parenchymal neurologic involvement (n=8), arthritis (n=1) and venous ulcer (n=1). Of these 50 patients, 22 (43%) are still receiving IFX for a median duration of 40 (IQR: 25-83) months. The remaining 28 (47%) patients had discontinued IFX after a median follow-up of 12 (IQR: 7-30) months. Reasons for discontinuation were remission in 7 patients, adverse events in 10, primary lack of efficacy in 2, and lack of patient compliance in 9 patients. Among the 7 patients who discontinued IFX due to remission, only 1 patient with uveitis had a flare, 11 months after discontinuation, while on azathioprine. The remaining 6 did not experience any flares during a median follow-up of 29.5 (IQR: 4-24) months. Five of these patients used azathioprine and 1 used mycophenolate mofetil for maintenance. Among the 10 patients who discontinued due to adverse events, IFX was switched to adalimumab in 3 patients and none experienced flares under adalimumab. The remaining 7 patients continued to receive azathioprine or mycophenolate mofetil without a biologic. Among these, 1 patient with uveitis 1 with arthritis experienced flares 6 months after discontinuing IFX. Among the 9 patients who discontinued IFX due to lack of patient compliance, 3 patients (2 with uveitis and 1 with arthritis) had flares after 5 months, 1 year and 1.5 years. IFX was re-initiated in all. The remaining 6 patients did not experience any flares after a mean follow up of 5±1.5 years. Two with uveitis and 2 with venous thrombosis used azathioprine for maintenance, while 2 patients did not receive further treatment. New major organ involvement was not observed. New BS manifestations developed in 2 patients under IFX, arthritis in one patient and both epididymitis and erythema nodosum in the other. Conclusion: Almost half of our patients with BS remained on IFX during a median follow-up of 5.4 years (IQR:2.4-7). Main reasons for discontinuation were adverse events, remission and lack of patient compliance. Our observations further support the efficiency of IFX in managing patients with BS. Disclosure of Interests: Sinem Nihal Esatoglu: None declared, Beyza Tukek: None declared, Sitki Safa Taflan: None declared, Yilmaz Ozyazgan: None declared, Didar Ucar: None declared, Emire Seyahi: None declared, Melike Melikoglu: None declared, Vedat Hamuryudan Speakers bureau: Pfizer, AbbVie, Amgen, MSD, Novartis, UCB, Ugur Uygunoglu: None declared, Aksel Siva: None declared, Izzet Fresko: None declared, Sebahattin Yurdakul: None declared, Hasan Yazici: None declared, Gulen Hatemi Grant/research support from: BMS, Celgene Corporation, Silk Road Therapeutics – grant/research support, Consultant of: Bayer, Eli Lilly – consultant, Speakers bureau: AbbVie, Mustafa Nevzat, Novartis, UCB – speaker